What Role Do Boards Play in Companies with Visionary CEOs? - JIANG, XU; LAUX, VOLKER (Journal of Accounting Research, 2024)
ABSTRACT Visionary CEOs have strong beliefs about the right course of action for their firms. How should a board of directors that does not necessarily share the visionary CEO's confidence advise and monitor the CEO? We consider a model in which the board can acquire costly information about the firm's optimal strategic direction. The board not only advises the CEO on strategy, but also must approve it, and the CEO exerts effort to implement the strategy. We find that the board gathers less information when the CEO believes more strongly in his vision. Further, depending on the strength of the CEO's belief bias, the board either plays an advisory role, a monitoring role, or a rubberstamping role. The model predicts that in firms that are led by highly visionary CEOs, boards are passive in that they acquire little information and rubberstamp the visionary's proposal. Nevertheless, shareholders prefer the visionary over an unbiased manager in industries in which obtaining information about the correct course of action is difficult and costly.